Phyllodes tumor in adolescent. Case study. - Lidia Torres Aja; Julio Sarmiento Sánchez; María Caridad Rubio Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Presentation of the case of a patient (18 years old) who was assisted in the provincial mastology consultation for a non painful tumor, of sudden growth covering almost all the right breast, without other symptom or sing. After some tests, it was decided to operate. The tumor turned to be benign phyllodes. The relevance of this case lies in the infrequent appearance of this type of tumor, being even the first to be operated in our hospital.